An intelligent orientation aid for the visually handicapped - Li, Elain Yee Lam (2019)
There are currently many assistive navigational systems to support the visually impaired community. However, there is a lack of available systems when it comes to navigating in indoor spaces such as shopping malls, school halls and ballrooms. This report studies the existing technologies used and the ways in which they are incorporated into current navigational systems, starting off with a detailed breakdown of fundamental components and methodologies used. Thereafter, it will also examine how navigation devices are being paired with different wireless technologies, like Wi-Fi, Bluetooth etc. to improve the overall efficiency and effectiveness of the systems and subsequently integrated into applications which are compatible with mobile devices. This report will also introduce the start of a new indoor navigational system project named ‘TheEye’, which is based off iBeacon technology. This technology will be explained in-depth, first covering the technical specifications and features of the hardware used. Then discussing the methodology of the hardware setup and finally, the software programming that was done to incorporate this whole technology into a navigational system which can be run as a mobile application. In addition, Arduino programming will be used to create a smart cane prototype aimed to provide a device for obstacle avoidance. Ultimately, in the discussion of future works for improvements that can be made to the project. The idea of iBeacon working in conjunction with Arduino to achieve the goal of independent navigation while avoiding obstacles successfully is proposed.